PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION KARYAWAN HOTEL GRAND ZURI PEKANBARU - Anggelisa Gabriella; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine how much influence the job satisfaction and organizational commitment to turnover intention. The sample in this study was taken as many as 95 respondents and the technique used is census technique. The data in this study using survey method through questionnaires filled by employees. Data were obtained using simple regression analysis and multiple regression analysis. The results of this study showed that job satisfaction had a negative and significant effect on turnover intention. Organizational commitment has a negative and significant effect on turnover intention. And simultaneously job satisfaction and organizational commitment have a significant effect on turnover intention. Subsequent research is suggested to use other methods in researching turnover intention, for example through in-depth interviews of respondents.Keywords: Job Satisfaction, Organizational Commitment, And Turnover Intention